Language teachers' conceptions of assessment: an Egyptian perspective. Issue 1 (1st January 2017) - Gebril, Atta
Abstract : The current study investigates the assessment conceptions of both pre-service and in-service English teachers within a high-stakes, test-driven context in Egypt. For this purpose, 170 Egyptian pre-service and in-service teachers completed an assessment conceptions questionnaire. Quantitative and qualitative data analysis were employed to answer the research questions. The results of the study showed in-service teachers preferring a combination of formative and summative assessment practices while pre-service teachers favored a relatively summative paradigm. With regard to functions of assessment, in-service teachers endorsed the improvement function of assessment more than the pre-service group. Both groups had negative perceptions about the effectiveness of teacher training programs. The study provides a number of implications for language teachers, teacher educators, and policy-makers.